2015
DOI: 10.3329/bjo.v20i2.22019
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Malignancy in solitary Thyroid nodule and Multi-nodular Goitre

Abstract: This cross sectional study with purposive sampling based on 50 cases of solitary thyroid nodule and multi-nodular goitre for operation in department of Otolaryngology and Head-Neck surgery of SSMC & Mitford Hospital, Dhaka and Dhaka Medical college, Dhaka during January 2009 to December 2009. Objectives of this study to find out relative frequency of malignancy in solitary thyroid nodule and multi-nodular goitre (by histopathology). Each case was studied by history taking, physical examination and relevant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 1 publication
5
9
0
Order By: Relevance
“…The proportion of PTC among thyroid cancer diagnosed in our study was 80.3%. It was lower than 98.5% noted in other study [21], but in concordant with previous study conducted in Bangladesh [12].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The proportion of PTC among thyroid cancer diagnosed in our study was 80.3%. It was lower than 98.5% noted in other study [21], but in concordant with previous study conducted in Bangladesh [12].…”
Section: Discussionsupporting
confidence: 91%
“…Prevalence of malignancy in our study was 20% among 120 thyroid nodule cases. The rate was in accordance with another study conducted in Bangladesh where the prevalence was 18% [12]. It was slightly higher than other studies conducted in ordinary thyroid nodules [48].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The mean age of patients with nodular thyroid enlargement was 36.4±13.4 years. A similar mean age of 36.9±12.2 years has been reported by Khan et al 16 20 reported these frequencies to be 24%, 66% and 10% respectively in Bangladesh 20 . There were 18(19.6%) male and 74 (80.4%) female patients with nodular thyroid enlargement with a male to female ratio of 1:4.1.…”
Section: Discussionsupporting
confidence: 80%
“…Hossain MA et al, observed that male to female ratio was 1:7 and the highest number of patients with thyroid nodule were found in age group 31-40years. 12 The relative frequency of malignancy in solitary thyroid nodule was 28%. Akhtar N et al, in their study noted that majority of the patients i.e.…”
Section: Discussionmentioning
confidence: 97%